World Economic Outlook, May 1986. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1986)
This paper describes the world economy in 1991 and balanced growth in industrial countries. The year 1985 has been somewhat disappointing from the viewpoint of economic growth. Expansion fell back by more than expected in the industrial world, and world trade increased only modestly. Macroeconomic policies in industrial countries are likely to be directed toward the medium-term objective of maintaining financial stability, while reducing the claims of governments on economic resources. Macroeconomic policies in developing countries reflect the considerable diversity of circumstances of the countries included in this group.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet